Fertility and pregnancy in cancer survivors. (September 2018) - Tang, Monica; Webber, Kate
Summary: Cancer survivors are increasing as improvements in cancer diagnosis and treatment translate to improved outcomes. As cancer survivors in their reproductive years contemplate pregnancy, it is important to understand the impact of cancer and its treatment on fertility and pregnancy outcomes. Cancer treatments such as chemotherapy and radiotherapy can affect patients' fertility, and strategies are available to help preserve the future fertility of survivors. The potential impact of previous cancer diagnoses and treatments on pregnancy and maternal and fetal outcomes needs to be assessed and discussed with survivors, with support from materno-fetal medicine specialists and high-risk antenatal services as needed.